Portal Vein Thrombosis - Ronny Cohen; Thierry Mallet; Michael Gale; Remigiusz Soltys; Pablo Loarte (Case Reports in Vascular Medicine)
Portal vein thrombosis (PVT) is the blockage or narrowing of the portal vein by a thrombus. It is relatively rare and has been linked with the presence of an underlying liver disease or prothrombotic disorders. We present a case of a young male who presented with vague abdominal symptoms for approximately one week. Imaging revealed the presence of multiple nonocclusive thrombi involving the right portal vein, the splenic vein, and the left renal vein, as well as complete occlusion of the left portal vein and the superior mesenteric vein. We discuss pathogenesis, clinical presentation, and management of both acute and chronic thrombosis. The presence of PVT should be considered as a clue for prothrombotic disorders, liver disease, and other local and general factors that must be carefully investigated. It is hoped that this case report will help increase awareness of the complexity associated with portal vein thrombosis among the medical community.